Creativity of Messages on Instagram Content of @Winngas as a Trigger for Brand Addiction for Their Followers - Salfiyah Vivi; Rusnoto Farady Marta; Muhamad Isnaini (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Instagram is one of the most commonly used social media in a company or institution in communicating company activities or activities with their respective goals. The digital era like today forces every marketer to be able to manage Instagram media so that it can be well received by consumers in order to create brand awareness. Winn Gas is a kitchen equipment brand that uses Instagram @winngas as a means of disseminating information about sales to consumers to increase brand awareness with creative message strategies that are created. Strategy based on Advertising approach, message appeal, execution framework and credibility of source or endorser. This study uses Holsti's qualitative content by paying attention to Instagram content from @winngas which is found in image content uploaded every day, plus by paying attention to Winn Gas's Instagram which protects with supporters. There are two endorsers to be studied, namely Chef Muto and Chef Devina Hermawan and Focus content taken from @winngas instargam posts categorized from product posts, mini quiz activities, holiday greetings, cooking content, events, interesting facts, creative message content. Posts are taken from a 30 day period represented by 10 Instagram posts. The results of the study show that the posts made by @winnga in the form of a creative message unit can increase brand addacition on social media Instagram